Clinical-epidemiological characterization and etiological agents of severe acute respiratory infections in adults in Paraguay - Montiel-Jarolin, Dora; Samudio, Margarita; Volkart, Karin; Leguizamón, Rosa; Jarolin, Magali; Torres, Estela; Sánchez, Luis (Medicina Clínica y Social, 2024)
Introduction: Sentinel Surveillance of Severe Acute Respiratory Infections (SARI) includes the monitoring and characterization of hospitalized cases. Objective: To describe the clinical-epidemiological characteristics and etiological agents of adults with SARI in a sentinel hospital in Paraguay. Methodology: Observational, descriptive, cross-sectional study, with retrospective data collection, of adult patients with SARI hospitalized at the National Hospital of Itauguá between June 2022 and August 2023. The information was taken from the database of the National System of Epidemiological surveillance. Results: The data of 1598 patients with SARI were analyzed, 820 men (51.3%), 875 (54.8%) aged 60 or older, 1054 (66.0%) from the Central department. 79.2% (n=1265) of patients had some risk factor or comorbidity, 764 with hypertension (47.8%). 38.5% (n=632) were admitted to the ICU and mortality was 34.7% (n=554). SARSCoV-2 was confirmed in 13.8% (n=353), rhinovirus (1.7%), influenza A (1.5%), influenza B (0.6%), parainfluenza 3 (0.6%), RSV (0.2%), bocavirus (0.4%) and Influenza AH1N1 (0.6%). There was a significantly higher frequency of deaths in those aged 60 years and over (40.7%), with some risk factor (35.5% vs 25.9%), and in those confirmed with covid-19 (38.2% % vs 30.5%). Conclusion: SARSCoV-2 continues to be the main etiological agent of SARI in a sentinel hospital in Paraguay. Continued knowledge of the epidemiology and viral agents involved is crucial to developing effective prevention and treatment strategies.